Prevalence of urinary tract infection in febrile preschool children - Singh, Swatantar; Parihar, Sangeeta (International Journal of Contemporary Pediatrics, 2019)
Background: Children with fever is a common and comprise a substantial proportion of the practice in outpatient department and emergency department. Little attention has been focused on the identification of urinary tract infection (UTI) in febrile in infants and children in the emergency department, despite recent information that suggests a high prevalence of urinary tract infections and significant associated morbidity in these patients. The present study is undertaken to estimate the prevalence of urinary tract infection in febrile preschool children (less than 5 years of age) in febrile children. Methods: Febrile children less than 5 years attending outpatient department or admitted in Department of Paediatrics were enrolled into the study. Children below 1 month and above 5 years; any child who has received antibiotics 48 hours prior to evaluation; children with known congenital genitourinary anomalies; and were excluded from the study. Children with symptoms suggestive of UTI were interviewed using structured case record form (CRF). All symptomatic children were referred for urine routine microscopy and culture tests. Results: The prevalence of culture positive cases for UTI was 6.36%. Male infants and female infants affected equally. But females affected more in the age between 1 years to 5 years as compared to males. Apart from fever, the commonest symptoms were dysuria, abdominal pain, vomiting, chills and rigors and loss of appetite. More than two-third of the patients with CP-UTI have E. coli as causative organism for UTI. Overall most sensitive antimicrobials were Ceftriaxone. Conclusions: UTIs in preschool children are often having vague and variable symptoms, often fever is the only symptoms. An untreated UTI can lead to subsequent damage and impairment of renal structure and function, it is very important to diagnose and treat UTI in preschool children.